Prognostic Significance of Baseline Clinical and [68Ga]Ga-PSMA PET Derived Parameters on Biochemical Response, Overall Survival, and PSA Progression-Free Survival in Metastatic Castration-Resistant Prostate Cancer (mCRPC) Patients Undergoing [177Lu]Lu-PSMA Therapy - Jafari, Esmail; Manafi-Farid, Reyhaneh; Ahmadzadehfar, Hojjat; Salek, Fatemeh; Jokar, Narges; Keshavarz, Ahmad; Divband, GhasemAli; Dadgar, Habibollah; Zohrabi, Farshad; Assadi, Majid (Nuklearmedizin - NuclearMedicine, 2024)
Background In this study, we sought to identify the clinical baseline characteristics and pre-therapy 68Ga-PSMA PET derived parameters that can have impact on PSA (biochemical) response, OS and PSA PFS in patients with metastatic castration-resistant prostate cancer (mCRPC) who undergo RLT with [177Lu]Lu-PSMA-617.Methods Various pre-treatment clinical and PSMA PET derived parameters were gathered and computed. We used PSA response as the criteria for more than a 50% decrease in PSA level, and OS and PSA PFS as endpoints. We assessed the collected parameters in relation to PSA response. Additionally, we employed univariable Cox regression and Kaplan-Meier analysis with log rank to evaluate the influence of the parameters on OS and PFS.Results A total of 125 mCRPC patients were included in this study. The median age was 68 years (range: 49–89). Among the cases, 77 patients (62%) showed PSARS, while 48 patients (38%) did not show PSA response. The median OS was 14 months (range: 1–60), and the median PSA-PFS was 10 months (range: 1–56). Age, prior history of chemotherapy, and SUVmax had a significant impact on PSA response (p<0.05). PSA response, RBC count, hemoglobin, hematocrit, neutrophil to lymphocyte ratio (NLR), alkaline phosphatase (ALP), number of metastases, wbPSMA-TV, and wbTL-PSMA significantly affected OS. GS, platelet count, NLR, and number of metastases were found to have a significant impact on PSA PFS.Conclusion We have identified several baseline clinical and PSMA PET derived parameters that can serve as prognostic factors for predicting PSA response, OS, and PSA PFS after RLT. Based on the findings, we believe that these clinical baseline characteristics can assist nuclear medicine specialists in identifying RLT responders who have long-term survival and PFS.
Keywords: Theranostics; [68Ga]Ga-PSMA; [177Lu]Lu-PSMA; Prostate cancer; Prostate specific antigen (PSA)